2019
DOI: 10.1111/jcmm.14661
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma japonicum peptide SJMHE1 suppresses airway inflammation of allergic asthma in mice

Abstract: Helminths and their products can shape immune responses by modulating immune cells, which are dysfunctional in inflammatory diseases such as asthma. We previously identified SJMHE1, a small molecule peptide from the HSP60 protein of Schistosoma japonicum. SJMHE1 can inhibit delayed‐type hypersensitivity and collagen‐induced arthritis in mice. In the present study, we evaluated this peptide's potential intervention effect and mechanism on ovalbumin‐induced asthma in mice. SJMHE1 treatment suppressed airway infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 48 publications
(115 reference statements)
3
37
0
Order By: Relevance
“…These data revealed a novel immune protective mechanism involving T cell epitopes from helminth-derived Th1-inducing antigens in modulating allergic asthmatic responses through an enhancing Th1 response ( 39 ). Also, the aforementioned peptide, SJMHE1, suppressed airway inflammation in the OVA-induced allergic asthma mouse model with modulation of pro- and anti-inflammatory cytokines in splenocytes and lungs, and decreased numbers of infiltrating inflammatory cells and eosinophils ( 40 ). SJMHE1 treatment during OVA sensitization and challenge in BALB/c mice significantly reduced the IL‐4 mRNA level in the splenocytes, suppressed the expression of IL‐4, IL‐5, and IL‐17 mRNA in the lungs, and increased IFN‐γ, IL‐10, and IL‐35 mRNA, indicating the suppressive effect was likely associated with decreased populations of Th2 and Th17 cells and an increased frequency of Th1 and Treg cells ( 40 ).…”
Section: Therapeutic Potential Of Live Schistosome Infection and Schimentioning
confidence: 99%
See 1 more Smart Citation
“…These data revealed a novel immune protective mechanism involving T cell epitopes from helminth-derived Th1-inducing antigens in modulating allergic asthmatic responses through an enhancing Th1 response ( 39 ). Also, the aforementioned peptide, SJMHE1, suppressed airway inflammation in the OVA-induced allergic asthma mouse model with modulation of pro- and anti-inflammatory cytokines in splenocytes and lungs, and decreased numbers of infiltrating inflammatory cells and eosinophils ( 40 ). SJMHE1 treatment during OVA sensitization and challenge in BALB/c mice significantly reduced the IL‐4 mRNA level in the splenocytes, suppressed the expression of IL‐4, IL‐5, and IL‐17 mRNA in the lungs, and increased IFN‐γ, IL‐10, and IL‐35 mRNA, indicating the suppressive effect was likely associated with decreased populations of Th2 and Th17 cells and an increased frequency of Th1 and Treg cells ( 40 ).…”
Section: Therapeutic Potential Of Live Schistosome Infection and Schimentioning
confidence: 99%
“…Also, the aforementioned peptide, SJMHE1, suppressed airway inflammation in the OVA-induced allergic asthma mouse model with modulation of pro- and anti-inflammatory cytokines in splenocytes and lungs, and decreased numbers of infiltrating inflammatory cells and eosinophils ( 40 ). SJMHE1 treatment during OVA sensitization and challenge in BALB/c mice significantly reduced the IL‐4 mRNA level in the splenocytes, suppressed the expression of IL‐4, IL‐5, and IL‐17 mRNA in the lungs, and increased IFN‐γ, IL‐10, and IL‐35 mRNA, indicating the suppressive effect was likely associated with decreased populations of Th2 and Th17 cells and an increased frequency of Th1 and Treg cells ( 40 ). While the suppressive mechanism involving the elevation of IL-10 in the allergic asthma mouse is different from that in the CIA model, schistosomes and their products modulate distinct targets regulating Th1/Th2/Th17-associated inflammation in the different models.…”
Section: Therapeutic Potential Of Live Schistosome Infection and Schimentioning
confidence: 99%
“…Briefly, apart from the control group, the mice were sensitized with 40 μg OVA ovalbumin (OVA, Sigma, Poole, UK) and 2 mg 10% aluminum hydroxide (Sigma) in PBS on day 0, 7, and 14 by intraperitoneal injection. From days 21 to 55, the sensitized mice were challenged with aerosolized OVA (5%) for 20 min in PBS as previously described [ 22 ]. Bronchoprovocation was performed in a vented plastic chamber (30 × 20 × 15 cm).…”
Section: Methodsmentioning
confidence: 99%
“…BALF was collected as previously described [ 22 ]. Briefly, left bronchial tubes of the mice were ligated, and the ice-cold PBS (0.5 mL) was instilled twice into the right lungs.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, contradictory results were also reported regarding the roles of regulatory T cells in schistosome mediated protection. Some studies showed that Treg was an important effector in schistosome mediated protection against asthma (21,23,(26)(27)(28), while a more recent study showed that the protection was independent of Treg (24).…”
Section: Introductionmentioning
confidence: 99%